Rapid, spontaneous obliteration of intracranial arteriovenous malformation. (December 2016) - Stetler, William R.; Polikfa, Adam J.; Fox, W. Christopher; Hoh, Brian
Highlights: Spontaneous thrombosis of arteriovenous malformations (AVMs) is rare. AVM thrombosis usually occurs after hemorrhage. AVMs prone to thrombosis are small with few arterial feeders/draining veins. Up-to-date imaging is recommended prior to intervention on AVMs. Abstract: A 35-year-old male presented with headaches and was found to have a Spetzler-Martin grade 2 right occipital arteriovenous malformation (AVM) with single, superficial draining vein. The patient opted to undergo embolization for possible cure with resection scheduled in the event complete obliteration was not achieved. Three weeks later, angiography during his embolization procedure revealed that the AVM had spontaneously obliterated; no treatment was required. In conjunction with prior case reports/series, this patient highlights the need for current imaging prior to proceeding with intervention to confirm that spontaneous obliteration has not occurred between diagnosis and treatment.